2011
DOI: 10.1088/0004-637x/743/2/116
|View full text |Cite
|
Sign up to set email alerts
|

Quark-Novae in Low-Mass X-Ray Binaries. Ii. Application to G87–7 and to GRB 110328a

Abstract: We propose a simple model explaining two outstanding astrophysical problems related to compact objects: (1) that of stars such as G87−7 (alias EG 50) that constitute a class of relatively low-mass white dwarfs which nevertheless fall away from the C/O composition and (2) that of GRB 110328A/Swift J164449.3+57345 which showed spectacularly long-lived strong X-ray flaring, posing a challenge to standard GRB models. We argue that both these observations may have an explanation within the unified framework of a Qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The major difficulty with the Fe-core hypothesis is that there is no conventional way in stellar evolution theory to produce iron-core white dwarfs with, in particular, masses less than the average mass as shown by the candidates in Figure 18. However, we draw the attention of the reader to the interesting suggestion of Ouyed et al (2011) who argued that, under certain circumstances, Fe-rich white dwarfs with masses in the range 0.43 < M/M ⊙ < 0.72 could be produced through quark-nova explosions in low-mass X-ray binaries. The predicted mass range is particularly suggestive in view of the results depicted in Figure 18.…”
Section: Iron-core White Dwarfs?mentioning
confidence: 99%
“…The major difficulty with the Fe-core hypothesis is that there is no conventional way in stellar evolution theory to produce iron-core white dwarfs with, in particular, masses less than the average mass as shown by the candidates in Figure 18. However, we draw the attention of the reader to the interesting suggestion of Ouyed et al (2011) who argued that, under certain circumstances, Fe-rich white dwarfs with masses in the range 0.43 < M/M ⊙ < 0.72 could be produced through quark-nova explosions in low-mass X-ray binaries. The predicted mass range is particularly suggestive in view of the results depicted in Figure 18.…”
Section: Iron-core White Dwarfs?mentioning
confidence: 99%
“…The idea of a QN in binaries has proven successful in accounting for some features of SNe-Ia (Ouyed et al 2014;Ouyed et al 2015) and Gamma Ray Bursters (Ouyed et al 2011c) and has been able to account for the LC of DES13S2cmm as shown here. Its ability in fitting properties of unusual SNe (see http://www.quarknova.ca/LCGallery.html) suggest that QNe may be an integral part of binary evolution; the QN could lead to novel and interesting evolutionary paths.…”
Section: Bh-accretionmentioning
confidence: 79%
“…Cheng & Dai (1996) then noted that these SSs were formed in low-mass X-ray binaries (LMXBs) during an accretion-triggered transition phase, which has been called a quark nova (QN) (Ouyed et al 2002). Similar to core collapse supernovae, SSs also gain post-QN kick velocity (Ouyed et al 2002;Keränen et al 2005;Ouyed et al 2011Ouyed et al , 2013. Thus, LMXBs are disrupted and IMSPs are formed.…”
Section: Introductionmentioning
confidence: 99%